SWOT ANALYSIS: INTERNAL AND EXTERNAL FACTORS ON INCREASING CONSUMPTION OF TRADITIONAL MEDICINE IN MEDAN CITY - Salsabila Salsabila; Aflahun Fadhly Siregar (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The level of public awareness of the importance of maintaining health is increasing. In addition, it also affected the standards and quality of medicine that people consumed. As a result, the need for medicines was getting higher, including traditional medicines, where the use of traditional medicines was generally considered safer and hereditary. In fact, the level of public consumption of traditional medicine was lower than traditional medicine. The objective of the study was to analyze internal and external factors in increasing the consumption of traditional medicine in Medan City. Respondents in this study were sellers of traditional medicine, the consumer of traditional medicine, the leader of Jamu’s enterpreneur Association,  and the supervisor  of food and medicine in The National Agency of Drug and Food Control (NA-DFC). The data analysis method used is SWOT analysis. The results show that the strategic position of increasing the consumption of traditional medicines in Medan is in quadrant I. Under these conditions, in general the strategy to increase the consumption of traditional medicines in the city of Medan is an aggressive strategy, namely by maximizing strengths to take advantage of existing opportunities. In detail, there were 11 alternative strategies that could be done which consist of SO strategy, WO strategy, ST strategy and WT strategy